Provocation: Is there an assumed need for participatory design with children? - Sim, Gavin (Interacting with computers, 2025)
Abstract This paper reflects on participatory design practices within the child–computer interaction (CCI) community, which has a long tradition of advocating the inclusion of children in the design process. The benefits of involving children are widely cited in the CCI literature. However, through a critical analysis of children’s current technology usage, research and industry practice, this paper offers three provocations relating to participatory design and children. The first focuses on what constitutes participatory design, suggesting that the use of children in a single design activity to generate ideas is very distant from traditional participatory design (PD) and thus should not be referred to as PD. the second is that there needs to be a shift toward researching and developing methods to enable children to participate in design activities that align with industry timelines. The final provocation suggests that unless there are some tangible benefits of including children in PD of technology or impact can be demonstrated from the work, then an ethical debate is needed about their role and inclusion. These three provocations are designed to question and stimulate the debate around the benefits and values of including children in the design process. Without a critical reflection on current practices and processes, current trends may continue and design practices within the industry may not evolve.